Criteria For Limiting Perpetrators And Victims In Pornography Crime - Danardono, Danardono; Agustanti, Rosalia Dika (Universitas Muhammadiyah Sumatera Utara, 2025)
The development of information and communication technology has had a positive impact on people's lives, but over time the forms of criminal acts have become increasingly diverse, from traditional to modern, one of which is the Crime of Pornography. The problem is how the factors influence the crime of pornography and what are the criteria for perpetrators and victims in the crime of pornography. This study uses a normative legal method with a statutory and conceptual approach. The result is that there are criteria for limiting perpetrators and victims in the crime of pornography, which can be said to be a perpetrator if everyone has been proven to produce, make, reproduce, duplicate, distribute, broadcast, import, export, offer, trade, rent and distribute pornography as regulated in the Pornography Law. Furthermore, it can be said to be a victim if someone becomes the object of a crime of Pornography, in addition, the victim is a person who experiences physical, mental, and/or economic suffering caused by a crime. A victim can also be said to be a perpetrator if he gives consent to the occurrence of a crime of pornography related to him. Therefore, there needs to be an update, especially in the Pornography Law which regulates the criteria for limiting perpetrators and victims, such as a victim can become a perpetrator if he/she agrees to commit a pornographic crime in addition to the perpetrator committing the crime as in Article 4 paragraph (1) of the Pornography Law. Thus, there needs to be a change in the Pornography Law to emphasize the role and limitations of perpetrators and victims so that this can provide legal certainty and benefits to perpetrators and victims of pornographic crimes